Electronic Health Record - Scarlat, Alexander (Productivity Press, 2012)
An accessible primer, Electronic Health Record: A Systems Analysis of the Medications Domain introduces the tools and methodology of Structured Systems Analysis as well as the nuances of the Medications domain. The first part of the book provides a top-down decomposition along two main paths: data in motion -workflows, processes, activities, and tasks in parallel to the analysis of data at rest -database structures, conceptual, logical models, and entities relationship diagrams. Structured systems analysis methodology and tools are applied to: electronic prescription, computerized physician order entry, drug dispensation, medication administration, and clinical decision support. Assuming no previous clinical and/or informatics knowledge, the book supplies a comprehensive view of the EHR/EMR with dedicated chapters on: user interface considerations, reporting requirements, and standards and vocabularies for meaningful use. Containing clear language and more than 170 figures and 100 review questions with answers-this book is a great companion for Healthcare IT professionals and an ideal resource for clinical informatics students. Praise for the book: ... a common sense guide to this new world of informatics ... should prove invaluable to the clinician making his/her way past the commercial hype into the realm of true understanding of the systems of medical informatics. ... strongly recommended ...-William F. Bria MD, CMIO Shriners Hospitals for Children, President of the Board, Association of Medical Directors of Information Systems Finally, here's a textbook that the market and the industry have been looking for. The author has captured the details of the information flows involved in the EHR while processing an order or prescription from inception to completion.-Joseph T. Finn, RPh, MBA ... a thoughtful and well-constructed manual to understanding and incorporating the complex and many-sided aspects of medication concepts ... a clear and accessible entry to this challenging topic.-Don Martin, Managing Consultant ... encompasses high-value, high-volume therapeutic transactions of indescribable complexity that touch nearly every licensed professional in a hospital ... I'm hoping the vendors of my own hospital's systems take its recommendations to heart.-Mr. HIStalk, Healthcare IT Blogger ... a very useful guide ... provides the necessary detail that is often missing in many books ... very useful in health informatics education at universities and courses with ...